Advanced serious illness, multimorbidity, and multibeneficence: The role of communication. Issue 6 (16th February 2017) - Cohn, Jeffrey
Abstract: Sturmberg et al write about multimorbidity as "several diagnosable diseases within the same individual."1 They posit that this syndrome is the result of multiple interconnected disturbances reflecting scale‐free, fractal signs of pathology ranging from biochemical/hormonal alterations at one end of a spectrum to community and societal ills at the other. In this commentary, I will be focusing on 3 perspectives: 1) a preterminal phase of multimorbidity that is indicative of that loss of reparative or even homeokinetic properties, known by some as "advanced serious illness"2 ; 2) the manifestations of advanced serious illness multimorbidity that, using the same networks that connect into the patient, are signs of this syndrome at the levels of the immediate family/friend social network, the broader community, and society at large; and 3) the potential for these same networks that transmit pathological forces to convey the positive effects of therapeutic interventions in a scale‐free manner, with a focus on how conversation can lead to what I'm calling "multibeneficence."